2020
DOI: 10.3390/ijerph17051647
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index (BMI) and Work Ability in Older Workers: Results from the Health and Employment after Fifty (HEAF) Prospective Cohort Study

Abstract: This study explores associations between BMI and prolonged sickness absence; cutting down at work; and health-related job loss (HRJL) over two years of follow-up among workers aged ≥50 years. A cohort of 2299 men and 2425 women (aged 50–64 years) self-reported height and weight at baseline and provided information about work ability at 12 and 24 months for the Health and Employment after Fifty (HEAF) Study. Associations between BMI and work ability were assessed by logistic regression and HRJL by multiple-reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…Similarly, existing evidence from previous studies shows that South Africa has the highest proportion of people who were overweight and obese among Coloured (26%) and Black/African population groups (20%), with the majority being women (14,35,43). Hence, the advancement of social change, urbanisation, and ageing could be the possible reasons for the key drivers of the prevalence of overweight/obesity among Black/African women in South Africa.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Similarly, existing evidence from previous studies shows that South Africa has the highest proportion of people who were overweight and obese among Coloured (26%) and Black/African population groups (20%), with the majority being women (14,35,43). Hence, the advancement of social change, urbanisation, and ageing could be the possible reasons for the key drivers of the prevalence of overweight/obesity among Black/African women in South Africa.…”
Section: Discussionmentioning
confidence: 73%
“…In view of this, binary outcomes with two possible values were constructed as the dependent variable for this study based on underweight vs. normal weight and overweight/obese vs. normal weight, respectively, based on the WHO standard BMI cut-offs ( 33 , 34 ). Thus, women who were underweight or overweight/obese were coded “1,” and those with normal weight were coded “0.” This categorisation was done to ensure large sample sizes for analyses and to obtain more robust binary logistic regression estimates ( 35 37 ). Women with BMI < 18.5 kg/m 2 were described as underweight, while those with BMI of 18.5–24.9 kg/m 2 were described as having normal body weight, those with BMI of ≥25 kg/m 2 were overweight, and those with BMI ≥ 30 kg/m 2 were obese.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase of one unit of health status decreases the productivity of -0.1045 for Column (2). The result is reaffirming (Goettler et al, Azra Tilai, Rayenda Khresna Brahmana and Hui Wei You 2017;Linaker et al, 2020;Marliyati et al, 2018) research, whereby the studies found that overweight and obesity to be associated with decreasing levels of productivity.…”
Section: Full Model Resultsmentioning
confidence: 58%
“…Farmers suffering from central obesity have a higher number of absent days due to health reasons than farmers not suffering from central obesity (Marliyati et al, 2018). According to Linaker et al (2020), people from lower socioeconomic positions are more likely to have physically demanding occupations. The implication is that obesity, yet another consequence of low social-economic position increases the risk of premature loss of personal economic productivity.…”
Section: H 1 : Higher Nutrition Leads To An Increase In Productivitymentioning
confidence: 99%